Cybersecurity and Innovation in the Evolving Digital Economy - de Percy, Michael (Journal of Telecommunications and the Digital Economy, 2025)
This editorial introduces the September 2025 issue of the Journal of Telecommunications and the Digital Economy, spotlighting the intersection of cybersecurity, emerging technologies, and historical lessons in the digital economy. As digital transformation accelerates, threats to IoT, cloud, and 5G ecosystems proliferate, demanding innovative, resource-efficient solutions for SMEs and emerging markets. Contributions in this issue – from machine learning-driven threat detection to zero-trust architectures and reflections on telecom automation – highlight human and organisational factors in resilience. They bridge legacy telecommunications with future-oriented strategies, underscoring the journal’s commitment to fostering adaptive digital ecosystems amid persistent vulnerabilities.